Correlation Between Nurse Time Management with Documentation of Nursing Care in The Inpatient Room of Muhammadiyah Hospital in Metro - Wulandari, Rizki Yeni; Yunitasari, Eva; Hakim, Arif Rahman; Prasandi, Adi (Universitas Aisyah Pringsewu, 2022)
Nursing documentation is necessary in the nursing care process. In Indonesia, nursing care documentation is still not up to standard, leading in issues with nursing care implementation, such as poor documentation of the quality of care provided in hospitals, making it difficult to verify that nursing care was administered correctly. Documentation of nursing care is an indicator of nurse performance which is influenced by nurse time management. The research objective was to determine the correlation between nurse time management and documentation of nursing care at the Muhammadiyah Hospital in Metro. This research was quantitative research, with a cross-sectional approach. The sample was 157 people taken by the purposive sampling technique. Univariate and bivariate data analysis used Spearman test correlation analysis (rho). From the results obtained from 61 respondents, it is known that nurses have good time management as many as 33 people (54.1%), and as many as 24 nurses (39.3) had enough time management. There is a correlation between time management and documentation of nursing care at the Muhammadiyah Hospital in Metro 2022, a value of p = 0.001 (p = less than 0.05). It is expected that the Muhammadiyah Hospital in Metro, especially for the nursing management, will be able to carry out regular checks on patient status or nursing records from assessment to evaluation, and can improve the quality of service in nursing by providing opportunities for nurses to take part in seminars on good time management and documentation of nursing care. Abstack: Dokumentasi keperawatan merupakan hal sangat penting dalam rangkaian asuhan keperawatan. Pendokumentasian asuhan keperawatan di Indonesia masih belum sesuai dengan standar sehingga muncul masalah dalam pelaksanaan asuhan keperawatan yaitu ketidaklengkapan dokumentasi asuhan keperawatan yang dilakukan di rumah sakit sehingga sulit untuk membuktikan bahwa asuhan keperawatan telah dilakukan dengan benar. Pendokumentasian asuhan keperawatan adalah indikator kinerja perawat yang dipengaruhi oleh manajemen waktu perawat. Tujuan penelitian ini untuk mengetahui hubungan manajemen waktu perawat dengan pendokumentasian asuhan keperawatan di Rumah Sakit Muhammadiyah Metro. Penelitian ini merupakan jenis penelitian kuantitatif, dengan pendekatan cross sectional sampel berjumlah 157 orang dengan teknik purposive sampling. Analisis data univariat dan bivariat dengan analisis korelasi uji spearman (rho).Hasil penelitian didapatkan dari 61 responden diketahui bahwa perawat memiliki manajemen waktu baik sebanyak 33 orang (54,1%), manajemen waktu cukup sebanyak 24 perawat (39,3). Ada hubungan hubungan manajemen waktu dengan pendokumentasian asuhan keperawatan di Rumah Sakit Muhammadiyah Metro Tahun 2022 nilai p=0,001 (p=kurang dari 0,05). Diharapkan bagi Rumah Sakit Muhammaadiyah Metro terutama bagi pihak manajemen keperawatan untuk dapat melakukan pemeriksaan secara berkala terhadap status pasien atau catatan keperawatan mulai dari pengkajian sampai evaluasi, serta dapat meningkatkan kualitas pelayanan dalam keperawatan dengan memberikan kesempatan bagi perawat mengikuti kegiatan seminar tentang manajemen waktu yang baik dan pendokumentasian asuhan keperawatan.